Effectiveness of Spencer Technique of Mobilization on Adhesive Capsulitis: A Single Case Study - Syeda Tofwiza Dayema; Wahida Ahmed; Prasenjit Bhattacharyya; Santosh Kumar Rajak (International Journal of Orthopedic Nursing and Practices, 2024)
Background: Frozen shoulder, or adhesive capsulitis, is a condition characterized by pain, restricted motion, and stiffness in the shoulder joint. This occurs due to inflammation and the thickening of the joint capsule. The Spencer technique, is a manual therapy method consisting of seven steps designed to improve shoulder function by enhancing joint mobility, circulation, and lymphatic flow. These movements target shoulder extension, flexion, circumduction, abduction, and adduction, to reduce stiffness and improve ROM. Objective: To investigate the effectiveness of Spencer technique on pain and ROM with adhesive capsulitis. Purpose: This study examines the effectiveness of Spencer technique on a patient suffering from frozen shoulder. Methodology: A single-case study, involved a 60-year-old patient with secondary Frozen Shoulder affecting the right shoulder post anterior dislocation of shoulder suffered 7 months back. The patient was non diabetic and had no apparent contra-indications for Spencer Technique. The patient’s ROM was limited, and pain was rated 7 on the Visual Analog Scale (VAS). Active ROM was measured using a goniometer for baseline value. The treatment included applying a moist hot pack for 20 minutes, followed by the Spencer technique where a series of seven steps to improving shoulder mobility. Starting with two sets of 10 repetitions, it increased to three sets in subsequent weeks. Sessions were held five times weekly, with weekly progress measurements. Result: In this study, a Spencer technique was applied to treat a patient with a frozen shoulder. The technique demonstrated significant improvements in shoulder ROM and VAS score decreased from 7 to 4, over a 3-week observation period. Conclusion: From this study we believe that the Spencer technique is a valuable therapeutic approach for enhancing shoulder function and reducing discomfort. Further research is needed to done for its broader applicability, effectiveness and long-term benefits across a larger patient population
Keywords: Frozen shoulder; adhesive capsulitis; manual therapy; restricted motion; spencer technique